Laporan draf awal-laporan kajian carrying capacity pulau-pulau peranginan negara, Semenanjung Malaysia - Asmawi, M. Zainora; Talib, Rosmin; Husain, Nooreha; Husin, Ahmad Tarmizi; Yahya, Zaki; Raja Othman, Raja Norashekin; Idrus, Rosli (PLANMalaysia, Pejabat Projek Zon Tengah, 2020)
The draft proposal report addresses the proposals of sectoral studies, including the spatial information, strategy, justification and details of the proposal. This would assist the relevant agencies in planning and developing the islands in a more sustainable manner, the priority is given not only to the social and economic growth of the tourism islands but also the environmental conservation is also the focus of the study. This is inline with the aspiration of SDG of the nation.